2016
DOI: 10.1007/s10763-016-9717-y
|View full text |Cite
|
Sign up to set email alerts
|

Science vs. Sports: Motivation and Self-concepts of Participants in Different School Competitions

Abstract: Competitions are discussed as a measure to foster students' interest, especially for highly gifted and talented students. In the current study, participants of a cognitive school competition in science were compared to non-participants of the same age group (14-15) who either did not participate in any competition or who participated in a non-cognitive sports competition. The study focused on goal orientations and competence beliefs and analyzed outcomes as a foundation for further improvements of enrichment m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…A wide range of studies have not only corroborated the BFLPE, but also found this positive relation of self-concept with achievement in mathematics and science (e.g., Antunes & Fontaine, 2013;Cvencek, Kapur, & Meltzoff, 2015;Jansen, Schroeders, & Lüdtke, 2014;Lee & Kung, 2018;Ma & Kishor, 1997;Sahranavard, Hassan, Elias, & Abdullah, 2012;Wang, Oliver, & Staver, 2008). Guided by this theoretical framework, Höffler et al (2017) and Chang and Lin (2017) found that also within a science Olympiad reference framework, participants' academic self-concept was significantly correlated with their academic achievement. 6.4.2 | Expectancy-value theory of achievement motivation Eccles et al's (1983) expectancy-value theory of achievement motivation aims to explain the mechanism behind choices and achievements, which allows for systematic analysis of concepts underlying decision-making (Eccles, 1994(Eccles, , 2005Wigfield & Eccles, 2000).…”
Section: Theories Used To Explain Participation and Achievement In mentioning
confidence: 77%
See 2 more Smart Citations
“…A wide range of studies have not only corroborated the BFLPE, but also found this positive relation of self-concept with achievement in mathematics and science (e.g., Antunes & Fontaine, 2013;Cvencek, Kapur, & Meltzoff, 2015;Jansen, Schroeders, & Lüdtke, 2014;Lee & Kung, 2018;Ma & Kishor, 1997;Sahranavard, Hassan, Elias, & Abdullah, 2012;Wang, Oliver, & Staver, 2008). Guided by this theoretical framework, Höffler et al (2017) and Chang and Lin (2017) found that also within a science Olympiad reference framework, participants' academic self-concept was significantly correlated with their academic achievement. 6.4.2 | Expectancy-value theory of achievement motivation Eccles et al's (1983) expectancy-value theory of achievement motivation aims to explain the mechanism behind choices and achievements, which allows for systematic analysis of concepts underlying decision-making (Eccles, 1994(Eccles, , 2005Wigfield & Eccles, 2000).…”
Section: Theories Used To Explain Participation and Achievement In mentioning
confidence: 77%
“…A wide range of studies have not only corroborated the BFLPE, but also found this positive relation of self‐concept with achievement in mathematics and science (e.g., Antunes & Fontaine, ; Cvencek, Kapur, & Meltzoff, ; Jansen, Schroeders, & Lüdtke, ; Lee & Kung, ; Ma & Kishor, ; Sahranavard, Hassan, Elias, & Abdullah, ; Wang, Oliver, & Staver, ). Guided by this theoretical framework, Höffler et al () and Chang and Lin () found that also within a science Olympiad reference framework, participants' academic self‐concept was significantly correlated with their academic achievement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These extracurricular activities can help students understand scientific concepts, raise interest in science and even nurture future scientists (Bellipanni and Lilly, 1999;Huler, 1991). Students who participate in science competitions, for instance, show a genuine interest in learning science (Abernathy and Vineyard, 2001;Czerniak and Lumpe, 1996), and both boys and girls develop the desire to understand scientific phenomena (Höffler, Bonin and Parchmann, 2016). Some experts argue that science clubs can also foster greater interest in science by emphasising the fun aspect of school science, especially among minority groups (Thomas, 1986;Yaakobi, 1981).…”
Section: Extracurricular Science Activitiesmentioning
confidence: 99%
“…Beyond school education, a large number of enrichment measures aim to identify such skills and interests in young people and to further support them-among them, science labs (de Jong, Linn, & Zacharia, 2013), summer schools (Markowitz, 2004), and science competitions (Höffler, Bonin, & Parchmann, 2017). However, it is an open question if or to what degree such enrichment measures actually achieve these goals, especially in a broader sense when not only highly gifted students are focused on (Stake & Mares, 2001).…”
Section: Introductionmentioning
confidence: 99%